New Strait Times , 27 April 2009 (The New Straits Times Press (M) Bhd, 2009)
World health authorities yestreday battled to contain a new killer swine flu blamed for dozens of death in Mexico amid fears it could mutate into a more deadly strain and spread around the globe.